2018
DOI: 10.1016/j.bbmt.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Additional Chromosome on the Clinical Outcomes of Hematopoietic Stem Cell Transplantation in Philadelphia Chromosome–Positive Acute Myeloid Leukemia in Adults

Abstract: The incidence of Philadelphia chromosome positivity (Ph) in adults with acute myeloid leukemia (AML) is very low. Ph AML is considered to be high risk for failure to attain remission or for early relapse after standard chemotherapy. Because of the low incidence of the disease, it has been difficult to determine the best treatment, including the effects of tyrosine kinase inhibitors. We retrospectively analyzed 29 patients with Ph AML (median age, 45 years; range, 18 to 80) managed at our center between 2002 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…However, our study evaluated a small TA B L E 2 Univariable analyses of overall survival, relapse, and non-relapse mortality rates after 3 years in acute myeloid leukemia (AML) with BCR::ABL1 group. and 44.4% in the MRD-negative and MRD-positive groups, respectively, before allo-HCT [21]. In addition, MRD-negative status before allo-HCT was reported to be associated with improved GVHD-free relapse-free survival [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, our study evaluated a small TA B L E 2 Univariable analyses of overall survival, relapse, and non-relapse mortality rates after 3 years in acute myeloid leukemia (AML) with BCR::ABL1 group. and 44.4% in the MRD-negative and MRD-positive groups, respectively, before allo-HCT [21]. In addition, MRD-negative status before allo-HCT was reported to be associated with improved GVHD-free relapse-free survival [8].…”
Section: Discussionmentioning
confidence: 99%
“…4,7,14 In a retrospective study from Korea on 29 patients with Ph + AML including 7 with additional inv(16), the CR rate was 81.5% following imatinib added to intensive chemotherapy. 17 Two recent studies from transplantation registries showed a better outcome in de novo patients who received an allogeneic stem cell transplantation. 18,19 In our study, the proportion of allografted patients (67%) may have contributed to the good outcome although the few non-transplanted patients did well too.…”
Section: Discussionmentioning
confidence: 99%
“…The five‐year OS rate was 69.3%. 10 Furthermore, Yılmaz summarized the ongoing trials recruiting CML‐MBP patients. The management of Ph + AML can refer to CML‐MBP because of the similar clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Min reported that 10 patients were treated with traditional chemotherapy combined with imatinib, and the median OS time was 6.5 months. 10 To the best of our knowledge, the combination of flumatinib and venetoclax has not been reported in clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation